Handbook for marine radio communication - Lees, Graham D.; Williamson, William G. (Routledge/Taylor & Francis Group, 2017)
This sixth edition has been fully updated to take into account major developments over the last five years, in particular the revised regulations introduced by the International Telecommunication Union in 2012. The authors deliver an authoritative guide to the complicated and changing world of radio communications. This is a definitive guide for today's maritime communications industry, including ship owners, ship managers, coast guards, seafarers, students of maritime communications, as well as the recreational sector.